Triaging Appointed-Counsel Funding and Pro Se Access to Justice - Barton, Benjamin H. (2012)
For decades, scholars and advocates have lauded Gideon’s guarantee of appointed counsel in criminal cases and sought to extend it into a civil-Gideon right in a range of civil cases. This past Term, the Supreme Court disappointed the civil-Gideon movement in Turner v. Rogers, unanimously rejecting an across-the-board right to counsel while encouraging reforms to make courts more accessible to pro se litigants. Turner is mostly right, we argue, because funding limitations require reserving counsel mostly for criminal cases, where they are needed most. For the first time, the Court recognized that lawyers can make cases not only slower and more complex, but also less fair. The better alternative, as Turner acknowledged, is less-expensive pro se court reform, rather than the impossible dream of giving everyone a lawyer. We offer some concrete suggestions on what legislatures, courts, legal-aid organizations, and others can do to further pro se access to justice